Объяснение:
1.
ответ: Б 15а³-6а².
2.
ответ: Б 8y⁵.
3.
ответ: A -2y⁴-2y³-2.
1. расскрываем скобки 2х^2-80=-x^2+6x+24+1
переносим 3х^2-6х-105=0
делим на 3 х^2-2х-35=0
Д=4+140=144
х1=7 х2=-5
2, 1/2xв квадрате -1/2-1/6 *2xв квадрате-5/6х=0
умножаем на 6 3*2xв квадрате-xв квадрате-5х-3=0
2 xв квадрате-5х-3=0
Д=25+24=49
х1=-1,5 х2=3
1. расскрываем скобки 2х^2-80=-x^2+6x+24+1
переносим 3х^2-6х-105=0
делим на 3 х^2-2х-35=0
Д=4+140=144
х1=7 х2=-5
2, 1/2xв квадрате -1/2-1/6 *2xв квадрате-5/6х=0
умножаем на 6 3*2xв квадрате-xв квадрате-5х-3=0
2 xв квадрате-5х-3=0
Д=25+24=49
х1=-1,5 х2=3
1. Б
2. Б
3.А-Б(А и Б ответы одинаковые, возможно опечатка)